2016
DOI: 10.1111/ppl.12483
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways regulated by abscisic acid, salicylic acid and γ‐aminobutyric acid in association with improved drought tolerance in creeping bentgrass (Agrostis stolonifera)

Abstract: Abscisic acid (ABA), salicylic acid (SA) and γ-aminobutyric acid (GABA) are known to play roles in regulating plant stress responses. This study was conducted to determine metabolites and associated pathways regulated by ABA, SA and GABA that could contribute to drought tolerance in creeping bentgrass (Agrostis stolonifera). Plants were foliar sprayed with ABA (5 μM), GABA (0.5 mM) and SA (10 μM) or water (untreated control) prior to 25 days drought stress in controlled growth chambers. Application of ABA, GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 78 publications
5
105
0
1
Order By: Relevance
“…Further studies are required to establish a role for phloem B-type cells in long-distance signaling in plants (Shelp, 2012). In a study concerning drought stress tolerance with a Poaceae species, Agrostis stolonifera , GABA was shown to enhance the accumulation of GABA and of other amino acids (glycine, valine, proline, 5-oxoproline, serine, threonine, aspartic acid and glutamic acid) (Li et al, 2017). Interestingly, in barley plants it was shown that external application of GABA was able to induce action potentials (APs) accompanied by cytoplasmatic acidification short of the position of the stimulus (Felle and Zimmermann, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are required to establish a role for phloem B-type cells in long-distance signaling in plants (Shelp, 2012). In a study concerning drought stress tolerance with a Poaceae species, Agrostis stolonifera , GABA was shown to enhance the accumulation of GABA and of other amino acids (glycine, valine, proline, 5-oxoproline, serine, threonine, aspartic acid and glutamic acid) (Li et al, 2017). Interestingly, in barley plants it was shown that external application of GABA was able to induce action potentials (APs) accompanied by cytoplasmatic acidification short of the position of the stimulus (Felle and Zimmermann, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…ASM treatment resulted in significantly increased accumulations of the amino acids aspartic acid, glutamic acid, glutamine, glycine, isoleucine, lysine, serine, and threonine during heat stress compared to untreated plants. Increased accumulations of the amino acids aspartic acid, glutamic acid, glycine, and serine have previously been associated with increased levels of stress tolerance in turfgrasses (Jespersen et al, 2015; Li et al, 2016). The higher accumulation of these amino acids in ASM treated plants may be part of major shifts in metabolism and activation of defense pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is evidence suggesting SA can influence the accumulation of some amino acids upon drought stress. A recent study focusing on drought in Creeping Bentgrass ( Agrostis stolonifera ) showed that SA conferred drought tolerance and also the accumulation of proline, serine, threonine and alanine (Li et al, 2016). However, an SA-influenced increased accumulation of carbohydrates, as noted in the Li et al (2016) study was not prominent in our results.…”
Section: Discussionmentioning
confidence: 99%